Pengembangan Modul Berbasis Keterampilan Proses Sains (KPS) pada Materi Sistem Organisasi Kehidupan Tingkat Sel - Fidelis Anggara Murdani Kolin; Desy Fajar Priyayi; Susanti Pudji Hastuti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2018)
The aims of this study are to develop a Science Process Skills Based Module (KPS) on Cell-Level Life Organization Materials for Grade VII Students of SMP Kristen 2 Salatiga. This research is a research development (R & D) with an F-D development model (Define, Design, Develop, and Disseminate), but in this study it does not cover the entire stages in the F-D development model, namely the disseminate stage because of the limitations of the time the research was conducted. The instruments in this study were interview sheets, validation sheets, and student response sheets. The results of module development research according to the expert validity test 3.1, test pedagogical validity 3.15, test the validity of practitioner experts 3.08, and limited field testing 3.37, from the overall data obtained shows that the average module values ​​above 3.00 and is categorized as "A " that is very good. Modules with the category "A" are feasible to use in class VII students in the learning process. Keywords: module, Science Process Skills (KPS)